Instrumentation for Dykes on Permafrost, Kettle Generating Station - Gupta, R. C.; Marshall, R. G.; Badke, D. (Canadian Geotechnical Journal, 1973)
Kettle Generating Station is the second hydro electric project built in northern Manitoba in the zone of discontinuous permafrost. Most of the dykes at the project are directly founded on permafrost affected materials. With the impounding of the reservoir the permafrost in foundations will eventually thaw resulting in settlement and possible slumping of dykes. Instruments were installed in all earthfill structures and foundations to monitor their short and long term behavior. In addition, intensive instrumentation was carried out in two selected areas to assist in defining the relationship between the rates of thawing of permafrost and drainage of free water. This paper describes the instrumentation program for dykes on permafrost, the selection of instruments and their installation, and gives the performance evaluation of some of the instruments.